Trajectories of delay discounting and smoking from adolescence to young adulthood - Dali, Gezelle; Poulton, Antoinette; Banaschewski, Tobias; Bokde, Arun L. W.; Desrivières, Sylvane; Flor, Herta; Garavan, Hugh; Grigis, Antoine; Heinz, Andreas; Martinot, Jean-Luc; Nees, Frauke; Orfanos, Dimitri Papadopoulos; et al. (Drug and alcohol dependence, 2025)
Background - Delay discounting is consistently implicated in nicotine use, with individuals dependent on smoking exhibiting greater discounting rates than those who do not smoke. The temporal relationship of delay discounting and smoking, however, has been relatively understudied as much of the existing literature has used cross-sectional designs. This study examined whether delay discounting is predictive of both the initiation of occasional smoking and the transition from occasional to daily use and whether escalating smoking behaviour predicts increased delay discounting. - Methods - Participants were drawn from the IMAGEN sample - a large, longitudinal, multicentre study. Data were collected at ages 14, 16, 18 and 22 years. Our sample consisted of 1668 participants (52 % female) who had completed at least two waves of data collection. Delay discounting was measured using the 27-item Monetary Choice Questionnaire. The European School Survey Project on Alcohol and Drugs (ESPAD) and the Timeline Follow-back were used to assess smoking behaviours. - Results - Higher delay discounting predicted a greater likelihood of initiation of occasional use but not the transition to daily smoking. The trajectory of smoking frequency was predicted by both baseline levels of delay discounting and the trend of delay discounting over time. Smoking, however, was not found to predict changes in delay discounting. - Conclusions - High delay discounting appears to precede the initiation of smoking and is predictive of the trajectory of smoking but may not distinguish between discrete states of smoking. Identifying heightened delay discounting in young people may offer the opportunity to prevent excessive smoking trajectories before they are initiated.
Online verfügbar: 8. November 2025, Artikelversion: 14. November 2025
Gesehen am 22.01.2026